Incorporating multifunctional value chain actors' varietal trait preferences in sweetpotato breeding programs: A pathway towards inclusive innovation - Okello, J.J.; Ojwang, S.O.; Otieno, D.J.; Mwanga, R.O.M.; Yada, B.; Campos, Hugo; Heck, Simon (2025)
CONTEXT: Conventional breeding programs have hitherto been farmer-centric, prioritizing improvement of agronomic traits while neglecting trait preferences of other value chain actors. The supply-side focus may lead to low adoption of new varieties and food insecurity. Inclusive breeding is vital for meeting diverse customer needs. OBJECTIVE: This study characterizes the multifunctional roles of sweetpotato actors and systematically assesses differences in varietal trait preferences among actors across the entire sweetpotato value chain in Uganda. It is premised on the CGIAR Excellence in Breeding platform’s guide to inclusive demand-driven breeding that espouses the need to involve a broad range of stakeholders in breeding program design, hence innovation development. It provides useful insights on varietal trait preferences and needs of actors that are essential to produce future fit-for-purpose market preferred innovations. METHODS: The study used a sequential mixed methods approach involving, first, systematic value chain-wide multidisciplinary consultations to elicit preferred sweetpotato traits. Second, collection of quantitative survey data from 1333 stakeholders identified primarily as producers (992), seed multipliers (68), processors (18), traders (97), and consumers (158). Third, a rigorous quantitative analysis to examine drivers of and trade-offs in varietal trait preferences by actor category. RESULTS AND CONCLUSIONS: The findings demonstrate the multifunctional roles of the actors and their varying trait preferences across the value chain. Actors with singular roles prioritize traits based on their immediate needs and commercial interests while those with joint roles exhibit a broader range of trait preferences. However, actors in both production and trading/consumption roles seek a balance between agronomic and quality traits, blending commercial and personal preferences. Regression analysis finds a higher preference for quality traits than agronomic traits as one moves downstream from producers to consumers. Mealiness is consistently preferred over agronomic and other quality traits. Also, overall, women have a balanced preference for both categories of traits. SIGNIFICANCE: The study demonstrates a rigorous participatory research process for eliciting strategic information for decision-making in breeding. It supports the need for systematic market intelligence in crop breeding systems to make them more pluralistic and responsive to evolving trait preferences across the value chain. Embracing multi-actor preferences with fit-for-purpose crop breeding innovations/products can foster uptake of the new varieties and benefit all value chain actors once the mix of trait preferences is fully accounted for in breeding programs and necessary efforts are put in place to ensure the new varieties are successful.